Image Processing, Bitrate Optimization, and Mobile Upload Efficiency - Farooq Abdulla Mulla (International Journal of Computational and Experimental Science and Engineering, 2026)
Media transmission efficiency is a growingly important issue in the modern mobile ecosystem as device imaging capabilities grow significantly beyond the network infrastructure limitations. High megapixel sensors and high frame rate video capture on Smartphones create large files of media that often surpass realistic transmission capabilities in cellular and wireless network settings. The use of advanced compression algorithms, smart bitrate control, and adaptive encoding schemes allows for reducing the file size significantly without compromising the visual quality that is not noticeable to human viewers in a wide range of content types. The format conversion, chroma subsampling, adaptive transcoding, and asynchronous processing architecture all minimize bandwidth usage and speed up the completion of media transmission under limited network conditions. Client-side processing deployment is a strategic distribution of computational load to mobile devices, which reduces the requirements of server infrastructure and improves user experience by reducing the transmission time. Quality evaluation systems based on a combination of complementary perceptual measures inform the choice of optimization parameters, which ensures uniform visual fidelity to a wide range of content and heterogeneous device platforms. New codec technologies, such as VVC and AV1, are expected to achieve significant efficiency gains to enable smooth media exchange at scale in resource-limited mobile computing devices.